Human Resource Measurement-A Challenge for Accountants. - Brummet, R. Lee; Flamholtz, Eric G.; Pyle, William C. (The Accounting Review, 1968)
The article focuses on the problems faced by the accountants in measuring human resources. Although financial reports do not recently provide the information necessary to answer all the questions related to this problem, a growing number of corporate managers are showing concerns that their accounting systems are not adequate. As corporate managers make expenditures which they justify as investments in human resources , accountants reflect them as immediate charges to income without considering the timing of expected benefits. Human resource information is essential for each of the several phases of management's planning and control functions. Management of human resources should assist in recognizing and defining problems . There is some evidence to indicate a degree of meaningful correlation between profitability of organizations and their expenditures on acquisition, training, and relation of human resource. This suggests that firms with a high human asset investment ration will ultimately generate high profits.